2021
DOI: 10.1111/plb.13240
|View full text |Cite
|
Sign up to set email alerts
|

Responses of growth, photosynthesis and related physiological characteristics in leaves of Acer ginnala Maxim. to increasing air temperature and/or elevated O3

Abstract: Regional warming and atmospheric ozone (O 3 ) pollution are two of the most important environmental issues, and commonly coexist in many areas. Both factors have an intense impact on plants. However, little information is available on the combined and interactive effects of air warming and elevated O 3 concentrations on physiological characteristics of plants.• To explore this issue, we studied variations in growth, photosynthesis and physiological characteristics of leaves of Acer ginnala seedlings exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…It has been reported that heat tolerance in chickpea is strongly associated with an increase in antioxidant enzyme activity and induction of heat shock proteins (Parankusam et al, 2017 ; Tao et al, 2020 ; Wang et al, 2021 ). Under combined stress, a significant increase in POD was found in D-09027 and CH24/07, while SOD activity remained similar as in control.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that heat tolerance in chickpea is strongly associated with an increase in antioxidant enzyme activity and induction of heat shock proteins (Parankusam et al, 2017 ; Tao et al, 2020 ; Wang et al, 2021 ). Under combined stress, a significant increase in POD was found in D-09027 and CH24/07, while SOD activity remained similar as in control.…”
Section: Discussionmentioning
confidence: 99%
“…Larch species are associated with ectomycorrhizal (ECM) fungi, which play a critical role in nutrient acquisition for their hosts [4,81,82]). In this study, we investigated species richness and diversity of ECM fungi associated with a hybrid larch (F 1 ) and its parents (Dahurian larch; L. gmelinii var.…”
Section: Effects Of Elevated O 3 Concentrations On Net Photosynthetic...mentioning
confidence: 99%
“…Without confounding changes in humidity, the stomatal response to higher ambient temperatures obviously showed increased stomatal opening in relation to O 3 flux [92,93]. Presently, the plant physiological characteristics resulting from the combined effects and interacting mechanisms of elevated O 3 and temperature are debatable [24,85,87,88,94,95].…”
Section: Plant Responses To Ozone Under Elevated Temperaturesmentioning
confidence: 99%